Cryopreservation of Terap (Artocarpus elasticus Reinw. ex. Blume) Seeds: Viability and Structural Characterization - Wardani, Fitri Fatma; Efendi, Darda; Suhartanto, Mohamad Rahmad; Purwoko, Bambang Sapta; Latifah, Dian (Journal of Tropical Crop Science, 2026)
Terap (Artocarpus elasticus Reinw. ex Blume) is an underutilized fruit tree native to Indonesia, valued both for its edible fruit and its diverse applications in traditional medicine. Terap seeds are recalcitrant, so cryopreservation is the most effective method for their long-term preservation. This study aimed to determine the optimal loading and vitrification times for cryopreservation to maintain seed viability. A factorial, completely randomized design was employed with two factors: loading time (0 and 20 min) and vitrification time (0, 30, and 60 min). Seed viability after loading and vitrification treatment with or without freezing in liquid nitrogen was evaluated using tetrazolium chloride (TTZ) and germination tests. Results indicated that the loading and vitrification treatments did not yet improve the viability of terap seeds after cryopreservation, as determined by the TTZ and germination tests. The TTZ test showed that the viability of all treated seeds decreased, regardless of whether they were frozen in liquid nitrogen. Germination tests revealed that all treated seeds without freezing had reduced germination, while none of the seeds treated with freezing germinated. Structural analysis indicated that freezing alters cell degradation, likely due to the formation of ice crystals and mechanical stress. To improve the success of terap seed cryopreservation, future efforts should focus on optimizing exposure times, reducing PVS2 toxicity, and enhancing cryoprotectant penetration by removing the seed coat or using the embryo axis as an explant.